Evaluation of cosmetic appearance of herniotomy wound scars in African children: Comparison of tissue glue and subcuticular suturing - Ademuyiwa, A. O. (Medknow Publications, 2009)
AIM: To evaluate the cosmetic appearance of herniotomy wound scars closed using either the tissue glue or subcuticular suturing technique. MATERIALS AND METHODS: Prospective randomised control study; randomisation into tissue glue and suturing groups. Ethical clearance obtained. Cosmetic outcome were based on visual analogue scale by parents and Hollander wound evaluation scale by a Plastic Surgeon blinded to the wound closure method. RESULTS: Fifty one wounds were evaluated, 26 in the tissue glue group and 25 in the suturing group. Parents' evaluation using Visual Analogue scale (VAS) showed that in the suturing group, 17 parents (68%) gave a VAS of 8cm while six parents (24%) gave a score of 7cm. Two parents (8%) gave a score of 9cm. In the tissue glue group, 22 parents (84.6%) scored the scar of their children as 8 or 9cm on the VAS while four parents (15.4%) gave a score of 7cm. The median VAS was 8cm for both groups with a range of 7 to 9cm. The Chi- square test showed that the parents preferred tissue glue compared with subcuticular suturing (X2 = 7.90, P < 0.05). The Hollander Wound Evaluation Scale (HWES) used by Plastic Surgeon showed 21 herniotomy wounds (84%) had a score of 6 in the suturing group while four wounds (16%) had a score of 5. In the tissue glue group, 19 wounds (73%) had a score of 6, six wounds (23.1%) had a score of 5 and a patient (3.8%) had a score of 4. The median score is 6 for both groups. There was no statistically significant difference between both groups (X(2) = 1.481, P = 0.393). CONCLUSION: This study has shown that the cosmetic outcome of wound closure using the tissue glue technique and subcuticular suturing technique are similar.